School Evaluation, the Model of the Balearic Islands - Bonnín Roca, Josep Lluís; Gomila i Benejam, Josep (Avances en Supervisión Educativa, 2023)
The paper presents the characteristics of the new model for evaluating schools that is being implemented in the autonomous community of Illes Balears. This model seeks to be comprehensive, encompassing all aspects related to the functioning of an educational centre, and focused especially on teaching-learning processes. Additionally, it seeks to give greater prominence to the school, promoting a process that begins with self-assessment and aims to have a direct impact on students as the main recipients of the continuous improvement process. The steps outlined in this model are detailed, which is divided into two phases: self-assessment and external validation by the Educational Inspection. The content of the tool developed for implementation is also described.